Fast response organic supramolecular transistors utilizing in-situ π-ion gels - Kushida, Soh; Smarsly, Emanuel; Wacker, Irene; Schröder, Rasmus R.; Bunz, Uwe H. F. (Advanced materials, 2021)
Despite their remarkable charge carrier mobility when forming well-ordered fibers, supramolecular transistors often suffer from poor processability that hinders device integration, resulting in disappointing transconductance and output currents. Here, a new class of supramolecular transistors, π-ion gel transistors (PIGTs), is presented. An in situ π-ion gel, which is an unprecedented composite of semiconducting nanofibers and an enclosed ionic liquid, is directly employed as an active material and internal capacitor. In comparison to other supramolecular transistors, a PIGT displays a high transconductance (133 µS) and output current (139 µA at −6 V), while retaining a high charge-carrier mobility (4.2 × 10−2 cm2 V−1 s−1) and on/off ratio (3.7 × 104). Importantly, the unique device configuration and the high ionic conductivity associated with the distinct nanosegregation enables the fastest response among accumulation-mode electrochemical-based transistors (<20 µs). Considering the advantages of the absence of dielectric layers and the facile fabrication process, PIGT has great potential to be utilized in printed flexible devices. The device platform is widely applicable to various supramolecular assemblies, shedding light on the interdisciplinary research of supramolecular chemistry and organic electronics.